Pengembangan TDR-IM Sistem Informasi Manajemen Keuangan Siswa di Pondok Pesantren: Integrasi, Simplifikasi dan Digitalisasi - Oktavia, Yelsi; Afifi, Abdullah A; Eliza, Mona; Abbas, Afifi Fauzi (Journal of Regional Development and Technology Initiatives, 2023)
The general problem of the difficulty of developing pondok pesantren is due to limited resources and an inaccurate interpretation of the position of pondok pesantren, in particular the improved management of the national education system and the 2019 UU No. 18 about Pesantren. The development of a student financial management system was carried out at PPM Perguruan Darulfunun El-Abbasiyah (Lima Puluh Kota, Sumatera Barat) using TDR-IM approach: 1) integration, 2) simplification, and 3) digitization. As a result of development, we have seen a significant increase in TDR components, especially data management components. The development of this student financial management system will improve the efficiency of operations and record keeping. This increase has also led to a more accountable and transparent student finance system. This student financial management system development also provides effective services, giving students and their legal guardians a planning guarantee for administrative expenses. The biggest obstacle in developing this financial management system is low literacy in general, especially in financial and technology literacy.